The Relationship Diet and Nutritional Status With The Menstrual Cycle at The Students of SMAN 13 Luwu - Musdalifah Musdalifah; Siti Saharia Rowa; Nadimin Nadimin (Jurnal Gizi dan Kesehatan Keluarga, 2023)
Malnutrition factors arise due to wrong diets such as overeating or eating unbalanced foods. Insufficient nutritional intake, causes menstrual irregularities in most young women. This study aims to determine the relationship between diet and nutritional status with the menstrual cycle in students of SMAN 13 Luwu. This study is an observational study with a Cross-Sectional study design. The sample was 138 students of SMAN 13 Luwu who were selected by simple random sampling. The diet was obtained through interviews using the food frequency questioinaire form. Nutritional status is obtained through weighing weight and measuring height based on Body Mass Index (BMI). The Menstrual Cycle is obtained through an interview using a questionnaire. The results showed that the diet is sufficient as much 39,9%, the diet is less as much 60,1%. Nutritional status is less by 31,2%, good nutritional status is 52,2%, nutritional status is more by 7,2%. A normal menstrual cycle of 78,3%, an abnormal menstrual cycle of 21,7%. The results of statistical tests between dietary variables and nutritional status with the menstrual cycle showed no relationship between diet and menstrual cycle and no relationship between nutritional status and menstrual cycle. Further research suggestions are expected for female students who have a deficient diet to improve their diet, pay attention to the type, amount and frequency of eating. For students who have abnormal nutritional status in order to be able to meet their nutritional intake according to their needs. For researchers, they can further examine the classification of diet less than adequate diet as well as nutritional status to further examine abnormal nutritional status compared to normal nutritional status so that more details can be obtained about the relationship between diet and nutritional status with the menstrual cycle.